Investigation of Soil Structure Interaction and Wall Flexibility Effects on Natural Sloshing Frequency of Vessels - Abbasi Maedeh, Pouyan; Ghanbari, Ali; Wu, Wei (Salehan Institute of Higher Education, 2017)
The main purpose of this study is to establish the effects of vessel walls flexibility on its natural sloshing frequency considering soil-structure-fluid interaction theory. Furthermore, two new efficiently relations to find both of wall flexibility and soil-structure interaction effects on natural frequency are developed. Regarding the aim of current study three different conditions of elevated tanks are applied. Fixed base condition with an emphasis on recommendations of international code ACI-350, analytical FSSI regarding equivalent mass spring method, and the numerical direct method regarding theory of finite element are taken into consideration. Results indicate that there is no significant effect of walls flexibility on natural sloshing frequency regarding fixed base assumptions of vessels. On the contrary, significant effects of wall flexibility are achieved considering SSI theory. Results of international code ACI-350 show that, the international codes assumptions have imprecise estimations of natural sloshing frequency in the range of hard to very soft soil categories.Â On the other hand, it is observed that the wall flexibility has a more highlighted effect on natural frequency in soft soils rather than soil-structure interaction. The significance of wall flexibility effect on natural frequency is more than that of SSI considering soil softening.